Menganalisis kemampuan komunikasi matematis siswa berdasarkan numerasi: implikasi untuk pembelajaran matematika - Anggraini, Bunga Ayu; Hanim Faizah (International Journal of Progressive Mathematics Education, 2025)
Purpose: This study aims to analyze the mathematical communication skills of elementary school students based on their numeracy levels within the context of the Least Common Multiple (LCM) to address disparities in conceptual understanding.Design/methodology/approach: A qualitative descriptive approach was employed, involving three fifth-grade students from SDN Manukan Kulon VI Surabaya. Subjects were selected via purposive sampling to represent low, medium, and high numeracy categories. Data were collected using numeracy and mathematical communication assessments.Findings: The results reveal a positive correlation between numeracy and mathematical communication. High-numeracy students demonstrate clear, logical, and systematic communication. Conversely, students in the medium and low categories exhibit significant weaknesses in explanation structure, mathematical terminology, and idea representation. Practical implications: These findings highlight the necessity of strengthening numeracy foundations to enhance mathematical communication and suggest the implementation of differentiated instruction in elementary education. Originality/value: This study contributes specific insights into how numeracy literacy underpins the formation of mathematical arguments in LCM topics at the primary level.   Purpose: Penelitian ini bertujuan menganalisis kemampuan komunikasi matematis siswa sekolah dasar berdasarkan tingkat kemampuan numerasi pada materi Kelipatan Persekutuan Terkecil (KPK) untuk mengatasi keragaman pemahaman konseptual. Design/methodology/approach: Menggunakan pendekatan deskriptif kualitatif dengan subjek tiga siswa kelas V-A SDN Manukan Kulon VI Surabaya. Subjek dipilih menggunakan teknik purposive sampling yang mewakili kategori numerasi rendah, sedang, dan tinggi. Instrumen utama meliputi tes numerasi dan tes komunikasi matematis. Findings: Hasil penelitian menunjukkan korelasi positif antara numerasi dan komunikasi matematis. Siswa berkemampuan numerasi tinggi menunjukkan komunikasi yang logis dan sistematis. Sebaliknya, siswa kategori sedang dan rendah mengalami hambatan pada struktur penyampaian, terminologi matematis, dan representasi ide. Practical implications: Temuan ini menekankan pentingnya penguatan basis numerasi untuk memperbaiki keterampilan komunikasi matematis, serta perlunya strategi pembelajaran terdiferensiasi di tingkat sekolah dasar. Originality/value: Studi ini memberikan perspektif spesifik mengenai bagaimana literasi numerasi mendasari pembentukan argumentasi matematis pada topik KPK di jenjang pendidikan dasar.